Meeting future NOX emissions using an electric heater in an advanced aftertreatment system - Meruva, Prathik; Matheaus, Andrew; Sharp, Christopher A.; McCarthy, James E.; Collins, Thomas A.; Joshi, Ameya (Frontiers in Mechanical Engineering, 2022)
Engine and aftertreatment solutions are being identified to meet the upcoming ultra-low NOX regulations on heavy duty vehicles published by the California Air Resources Board (CARB) and proposed by the US EPA for the year 2027 and beyond. These standards will require changes to current conventional aftertreatment systems for dealing with low exhaust temperature scenarios. One approach to meeting this challenge is to supply additional heat from the engine; however, this comes with a fuel penalty which is not attractive and encourages other options. Another method is to supply external generated heat directly to the aftertreatment system. The following work focuses on the later approach by maintaining the production engine calibration and coupling this with an electric-heater (EH), light-off Selective Catalytic Reduction (LO-SCR) followed by a primary aftertreatment system containing a DPF and SCR. External heat is supplied to the aftertreatment system using an EH to reduce the tailpipe NOX emissions with minimal fuel penalty. This method has been implemented on multiple aftertreatment configurations and one of the configurations addresses the real-world packaging options for the LO-SCR. Future work will add Cylinder De-Activation (CDA) system to the engine to reduce fuel consumption (with a goal of net fuel reduction) and improve aftertreatment temperature.